Sistem Informasi Manajemen Kepegawaian Penentuan Karyawan Terbaik Menggunakan Metode Analytical Hierarchy Process (AHP) Di PT.Nerangi Sarana Karya Berbasis Web: (Studi kasus : PT. Nerangi Sarana Karya) - Haris Ihsanil Huda; Hendri Rasminto; Indra Ava Dianta (Pusat Riset dan Inovasi Nasional, 2023)
In the era of information and technological developments that are very rapid as it is today, in the context of managing human resources in a company or what is known as a personnel management information system.The problems faced by PT. Manage the work facilities, namely until now, the personnel data management is still using a manual system that has not been properly computerized, does not have a database as a data storage medium, does not share data over the network and still uses hardcopy printouts.Seeing the problems that occur in the personnel administration subdivision of PT. Serang the means of work, the author intends to develop a web-based personnel information system (SIMPEG) to handle staffing master data, employee data, promotion data, and periodic salary increase data. using PHP and MySQL. The system development method that I use is AHP.In the end, this system can provide output to its users in the form of a promotion decree, a regular salary increase decree and employee reports. Employee Recapitulation Report. Promotion report. Periodic salary increase reports